2020
DOI: 10.18632/aging.103057
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and successful aging among middle-aged and older adults: a systematic review and meta-analysis of cohort studies

Abstract: Aging is a global problem. According to the World Health Organization's report about global health and aging, the number of people aged ≥ 65 will increase to approximately 1.6 billion in 2050 and comprise 16% of the world's population [1]. Aging is associated with health-related problems and substantial medical cost. Disease patterns among the elderly also shift to chronic non-communicable diseases such as cardiovascular disease, hypertension, diabetes, cancer, and dementia [1]. In the US, England, and Europe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 44 publications
3
52
1
5
Order By: Relevance
“…Consistent with studies 12 , 17 19 , this study showed a positive association between physical activity, daily Yoga practice and SA. In a systematic review Yoga practice was found to be associated with better subjective health and health behaviours 35 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with studies 12 , 17 19 , this study showed a positive association between physical activity, daily Yoga practice and SA. In a systematic review Yoga practice was found to be associated with better subjective health and health behaviours 35 .…”
Section: Discussionsupporting
confidence: 90%
“…Sociodemographic factors associated with SA may include younger age 8 , 11 , 12 , male sex 8 , 11 , 12 , married 12 , spouse accompany 8 , higher education 3 , 7 , 8 , 10 , 12 15 , higher income/wealth 8 , 12 14 , higher childhood wealth 15 , ethnicity 7 , region 10 , and urban residence 16 . In addition, various health behaviours have been found associated with SA, including not smoking 17 , alcohol drinking 8 , physical activity 12 , 17 19 , healthy diet 20 , cognitive activity 12 , and a normal body mass index 17 . Studies on SA among older adults have largely been conducted in high-income countries, except for China.…”
Section: Introductionmentioning
confidence: 99%
“…Underweight has been found associated with poorer health outcomes [37], and low BMI was associated with nonsurvival [38]. However, in contrast with previous research [8,12,[17][18][19][20], we did not find an association between alcohol use, physical activity, dietary behaviour and HA.…”
Section: Discussioncontrasting
confidence: 99%
“…Sociodemographic factors associated with HA may include younger age [8,11,12], male sex [8,11,12], higher income/wealth [8,[12][13][14][15], ethnicity [7] and urban residence [16]. In addition, various health behaviours associated with HA have been found, including not smoking [17], alcohol consumption [8], physical activity [12,[17][18][19], healthy diet [20] and a normal body mass index [17]. Studies on HA among older adults have been conducted primarily in high-income countries, except China.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) and exercise are considered powerful behaviors for reducing the risk of developing a myriad of chronic diseases ( de Souto Barreto et al, 2017 ; Lee et al, 2012 ; Nyberg et al, 2020 ; Moore et al, 2016 ; Kivimäki et al, 2019 ) and to slow down the age-related progression of the disabling cascade, such as frailty ( Abe et al, 2020 ), functional limitations and disability ( GBD 2017 Risk Factor Collaborators, 2018 ; Sanchez-Sanchez et al, 2020 ; Tak et al, 2013 ), and early mortality ( GBD 2017 Risk Factor Collaborators, 2018 ; Saint-Maurice et al, 2020 ). Since PA and exercise benefit so distinct diseases, such as cancer ( Moore et al, 2016 ), Alzheimer’s and related diseases ( Kivimäki et al, 2019 ), heart conditions ( Colpani et al, 2018 ), they can be seen as one of the best interventions for healthy aging from both epidemiological ( Lin et al, 2020 ) and gerosciences perspectives ( Ferrucci et al, 2016 ; Rebelo-Marques et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%